The Effectiveness Of A Counseling Program Based On Multimodal Therapy In Enhancing Positive Thinking Among Deaf University Students. - Sabbah, Thaira; Al-Sarafandi, Yahya; Ibrahim, Ablah (International Humanities Studies, 2026)
This study aimed to examine the effectiveness of a counseling program based on multimodal therapy in enhancing positive thinking among deaf students at the university level. The study approached the literature as a multi-dimensional phenomenon, which addressed both theoretical and applied research. This recent study is the first, which dealt with this theme, to the authors' knowledge, which in turn encourages other researchers to work on further research on this important topic. The study used the experimental approach, in a cross-sectional study, using the sampling survey method. The Positive Thinking Scale is appropriate for the exploratory nature of the research. Ten deaf students from Al-Quds Open University, at Ramallah and Al-Bireh Branch were purposively selected, who obtained the lowest scores on the Positive Thinking Scale. The findings of the study revealed statistically significant differences in the mean scores of the experimental group on the post-test measure of positive thinking. Implications of the findings and directions for future empirical research are briefly discussed.